MANAGEMENT CONTROL OF GRASS-FED BEEF IN THE SEMIARID PAMPAS (Perspectivas de las Ciencias Económicas y Jurídicas, 2019)
One of the objectives of this work is to propose a quantitative model of management analysis aimed at evaluating the viability of endeavors dedicated to beef production an located in the semi-arid plains. For this purpose, we take into account standards and parameters related to technical, productive, economic and accounting issues. In other words, this proposal is based on the interaction of variables not only taken from the technical aspects emerging from biological cycles, but also considering the price and cost of factors associated to agricultural management. It should be noted that the mathematical model proposed in this work is applicable to a particular productive approach or management cycle related to the production of beef in the semi-arid pampas. That is to say, considering the productive process in its completeness, from the birth of the calf to its grass feed finishing for subsequent commercialization.In this first stage, the agroecological conditions of the semi-arid pampas and the different types of production that we can find were surveyed and analyzed; the characteristics of the product or value offered and its marketing conditions were also considered. Likewise, a complete cycle system of beef production was identified, together with its technical and productive of efficiency indicators, applicable to the Hilton Quota parameters. Finally, we will consider accounting and economic indicators that could be used to measure and weight prices and related costs.Based on the information gathered, we conclude that the quantitative model to be developed is applicable to the production of beef commercialized through the Hilton Export Quota. The model will consider the productive potential of each region and from this, the calculation of livestock equivalences and estimated weight gains will be made. Based on this, a breeding plan will be defined, which will be located in the "Caldenal" area and a wintering and finishing plan that will be located in the "Pampa Medanosa" area in the northeast of the province.To equalize the supply and demand of forage and meet the nutritional needs throughout the year, the amount of hectares needed for both plans will be determined taking into account the potentiality and productive stability of the agroecological regions indicated above. In order to determine the economic results and its accounting measurement, the income, the direct and the indirect costs will be taken into account. Also, for the purpose of computing the opportunity cost of the land, its lease value will be included. To value inventories or stock of animals at the end of the commercial year,  we will use the market value, the net realization value or the replacement depending on each particular case. Finally, projected annual profitability indices will be determined based on certain estimates of prices, revenues and costs.
Keywords: grass-fed beef; management control; math model of beef production; managerial indicators